(untitled) (Research, Society and Development, 2021)
Objective: to investigate the knowledge of nursing residents at the Federal University of Rio de Janeiro regarding the reading and recording of the chemical indicator used inside the boxes and packages of surgical instruments and health products. Methodology: a descriptive study, with a quantitative approach, carried out with resident nurses at the Federal University of the State of Rio de Janeiro. Inclusion criteria: being a nurse and nursing resident at UNIRIO with active enrollment. An instrument sent by electronic mail was used. The collected data were categorized and stored in an Excel® spreadsheet. The professional profile of the sample was described by absolute and relative frequencies of categorical variables. The proportion of agreement of resident nurses was calculated, with regard to the statements presented in the instrument for their analysis. (CAAE: 39525820.7.0000.5285). Results: 43 nurses answered the questionnaire, aged between 25 and 28 years, mostly female and graduated between 1 and 5 years. It was observed that 74% of resident nurses considered themselves capable of reading the chemical indicator. Conclusion: it is concluded that resident nurses have the knowledge and security to evaluate the result of a chemical indicator type 5 or 6 and feel able to evaluate it.